A new weak area identification method in power system based on voltage stability - Aziz N.F.A.; Rahmat N.A.; Muhammad-Sukki F.; Rahman T.K.A.; Yasin Z.M.; Wahab N.A.; Salim N.A. (Universiti Teknikal Malaysia Melaka, 2023)
Identification of voltage stability weak area in power system plays an important role in preventing the occurrence of voltage collapse. A fast and accurate identification method helps power system operators to apply voltage stability control action on the weak area and thus avoids voltage collapse. This paper presents a new technique for weak area identification in a power system based on voltage stability named as Weak Area Indicator (WAI). WAI is derived from a newly developed voltage stability index, Voltage Stability Condition Indicator (VSCI). For verification purpose, the proposed WAI was tested with the existing method in the literature that used voltage stability variation method to detect weak area. Test results show that the proposed WAI is able to cluster weak areas correctly. All methods were tested on IEEE 30-bus and IEEE 118-bus test system.